A combination of nutrition and genetics is able to reduce age at puberty in Nelore heifers to below 18 months - Ferraz, M. V.C.; Pires, A. V.; Santos, M. H.; Silva, R. G.; Oliveira, G. B.; Polizel, D. M.; Biehl, M. V.; Sartori, R.; Nogueira, G. P. [UNESP] (Elsevier, 2018)
Nelore heifers usually begin their reproductive life at ≥24 months of age mainly due to suboptimal nutritional conditions and genetics. This study aimed to determine the effect of expected progeny difference (EPD) for age at first calving and average daily gain (ADG) on puberty in Nelore (Bos taurus indicus) heifers. A total of 58 weaned heifers (initial BW=174±6 kg; age=9±1 months) were allocated into 28 feedlot pens. Heifers were born from four sires, of which two had low EPD for age at first calving (L; n=33) and two had high EPD for age at first calving (H; n=25). Then, heifers of each EPD were randomly assigned to high ADG (HG; 0.7 kg) or low ADG (LG; 0.3 kg), resulting in four treatments: heifers from L sires were submitted to either HG (LHG; n=17) or LG (LLG; n=16), and heifers from H sires were submitted to either HG (HHG; n=12), or LG (HLG; n=13). The HG heifers were fed a 75% grain diet, whereas the LG heifers received 93% of forage in their diet. Blood samples were collected at 9, 14, 18, 24 and 28 months of age for IGF1 and leptin determination. There was a treatment effect (P<0.01) on the proportion of heifers that attained puberty by 18 (62%, 0%, 0% and 0%), 24 (100%, 6%, 54% and 0%) or 36 (100%, 100%, 100% and 38%) months of age for LHG, LLG, HHG and HLG treatments, respectively. In addition, mean age at puberty was different across treatments (P<0.01). Heifers from the LHG achieved puberty at the earliest age when compared with cohorts from other treatments (18.1, 28.9, 23.9 and 34.5 months for LHG, LLG, HHG and HLG, respectively). Serum IGF1 concentrations were higher for L heifers compared with H cohorts at 9, 14, 18, 24 and 28 months of age (P<0.01; treatment×age interaction), whereas circulating leptin concentrations were higher (P<0.01; age effect) as heifers became older, regardless of the treatments. In conclusion, only Nelore heifers with favorable genetic merit for age at first calving were able to attain puberty by 18 months of age. In heifers with unfavorable genetic merit for age at first calving, supplementary feeding to achieve high ADG was unable to shift the age at puberty below 24 months.
Keywords: age at first calving; Bos taurus indicus; IGF1; leptin; nutrition